Azure Active Directory for Secure Application Development : Use Modern Authentication Techniques to Secure Applications in Azure - Zaal, Sjoukje (Packt Publishing, Limited, 2022)
Develop secure applications using different features of Azure Active Directory along with modern authentication techniques and protocols Key Features Confidently secure your Azure applications using the tools offered by Azure AD Get to grips with the most modern and effective authorization and authentication protocols Unlock the potential of Azure AD's most advanced features including Microsoft Graph and Azure AD B2C Book Description Azure Active Directory for Secure Application Development is your one-stop shop for learning how to develop secure applications using modern authentication techniques with Microsoft Azure AD. Whether you're working with single-tenant, multi-tenant, or line-of-business applications, this book contains everything you need to secure them. The book wastes no time in diving into the practicalities of Azure AD. Right from the start, you'll be setting up tenants, adding users, and registering your first application in Azure AD. The balance between grasping and applying theory is maintained as you move from the intermediate to the advanced: from the basics of OAuth to getting your hands dirty with building applications and registering them in Azure AD. Want to pin down the Microsoft Graph, Azure AD B2C, or authentication protocol best practices? We've got you covered. The full range of Azure AD functionality from a developer perspective is here for you to explore with confidence. By the end of this secure app development book, you'll have developed the skill set that so many organizations are clamoring for. Security is mission-critical, and after reading this book, you will be too. What you will learn Get an overview of Azure AD and set up your Azure AD instance Master application configuration and the use of service principals Understand new authentication protocols Explore the Microsoft Identity libraries Use OpenID Connect, OAuth 2.0, and MSAL to make sign-in fully secure Build a custom app that leverages the Microsoft Graph API Deploy Azure AD B2C to meet your security requirements Create user flows and policies in Azure AD B2C Who this book is for If you are a developer or architect who has basic knowledge of Azure Active Directory and are looking to gain expertise in the application security domain, this is the book for you. Basic Azure knowledge and experience in building web applications and web APIs in C# will help you get the most out of this book.